The use of total quality management practices for halalan toyyiban of halal food products: exploratory factor analysis / Rizuwan Abu Karim …[et al.] - Abu Karim, Rizuwan; Mahmud, Nurazree; Abu Hasan, Helmy Fadlisham (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2020)
Much has been written on the influence of total quality management (TQM) towards ensuring quality of food products. To date, however, there seems to be lack of research examining the influence of TQM practices towards halalan toyyiban of halal food products. Based on the Malcom Baldrige National Quality Awards (MBNQA) model, strategic planning, information management, top management, process management, human resource and customer focus were the six dimensions of TQM practices proposed in this study. A total of 128 certified halal food manufacturers were involved in this study. Exploratory factor analysis (EFA) was applied to extract TQM practices. Findings indicated that strategic planning, information management, top management, process management, human resource and customer focus are six dimensions of TQM practices that can assure halalan toyyiban of halal food products.